Nanyang venture formula 1: testing and performance evaluation of formula vehicle under FSAE on-track regime - Yip, Seng Han (Nanyang Technological University, 2023)
This FYP report details the assembly and setup of the steering, drivetrain and suspension systems and the testing and data analysis of NTUs first FSAE car, the NVF-1. The report began with the assembly and modification of systems previously designed by seniors who graduated. Work was put into these systems to remedy certain flaws and to get them to fulfil the competition rules. Vehicle dynamics study was done to better understand the effect of steering geometry and suspension setup for vehicle optimization. The report goes into the details of the test run planning as well as data acquisition using instrumentation such as the IMU and GPS. The test runs were documented in this report in detail. The data gathered was analysed to form a baseline for future testing. The project is far from over as the NVF-1 still has huge potential for further optimization. The author hopes that the findings in this report will prove useful for future generations of NVF cars.